Discrepancies in how the impact of gout is assessed in outcomes research compared to how health professionals view the impact of gout, using the lens of the International Classification of Functioning, Health and Disability (ICF). Issue 9 (September 2016) - Kool, Eveline; Nijsten, Marieke; van Ede, Annelies; Jansen, Tim; Taylor, William
Abstract The International Classification of Functioning, Disability and Health (ICF) provides a common language to understand what health means. An ICF core set, a list of ICF categories affected by a certain disease, is useful to objectify the content validity of a health status measurement. This study aims to identify the potential items of a gout specific 'ICF core set'. A three-round Delphi exercise was conducted, using web-based questionnaires. Health professionals, specialized in gout, nominated and subsequently rated the relevance of life areas divided into ICF categories. Agreement was determined by using the UCLA/RAND criteria. Simultaneously, a systematic review of gout measure outcomes was conducted. The results of these studies were compared using the second level of the ICF categories. In the Delphi study, consensus was found for 136 relevant ICF categories. The literature study extracted 134 different ICF categories in 149 articles. Three hundred and ten were non-defined outcomes. A large number of ICF categories were deemed to be relevant for people with gout. Only 29.7 % (19/64) of the level 2 categories, deemed to be relevant by health professionals, had been assessed as relevant in at least 5 % of gout outcome studies. Conversely, 70 % (19/27) of level 2 ICF categories assessed in at least 5 % of outcome studies were deemed relevant by health professionals. These ICF codes, which are found relevant in both studies, should be considered as mandatory in further research to a validated and practical core set of ICF categories. Published gout outcomes research fails to evaluate many life areas that are thought relevant by health professionals.